Strategi Manajemen Pengembangan Ekowisata di Kawasan Sikabung-Kabung: Langkah Awal Menuju Desa Wisata Mandiri: Indonesia - Marpaung, Arif Pratama; Putri , Shella Sauna; Harahap, Afandi Oloan; Rachma, Yulia; Sadewo, Muhammad Prasono (UII, 2025)
Tourism development in Suka Makmur Village aims to create a sustainable ecotourism destination by utilizing the potential of local nature and culture. The process begins with a preparation and socialization stage involving community deliberations to align perceptions regarding the development model of the Sikabung-Kabung area. Community involvement in this discussion ensures broad support for the development of ecotourism-based tourism that utilizes the attractions of clear river flows and local products. The training provided improves community skills in ecotourism management and digital promotion, expanding marketing reach and attracting more visitors. The results of this training are reflected in the increase in the number of tourists thanks to more effective promotion and more professional management. The development of infrastructure such as parking lots, toilets, and prayer rooms, as well as environmental conservation efforts through reforestation, support visitor comfort and ecosystem sustainability. This program has successfully combined tourism development with environmental and local cultural preservation, offering greater economic benefits while ensuring long-term sustainability.